(untitled) (Economic and Political Thought, 2017)
The article is of a theoretical nature and is based on a comparative analysis of the literature on the subject. Its aim is to present the synthetic characteristics of those of firm theories (economic ones and management concepts related to them) which are most important for the description of negotiation processes in a company, as well as to show for what purposes these theories can be used in the area under consideration. Undertaking the above-mentioned objectives is justified by the need, on the one hand, to create theoretical foundations of the precise and comprehensive identification and analysis of negotiation processes in the enterprise and, on the other hand, to provide the necessary conditions for the efficient execution of these processes, i.e. their planning, conducting and summing up. In the subsequent part of the paper the following theories are characterised: of inter-organisational relationships, transactional costs, stakeholders, contract and agency. The presentation of each of them comprises two components: its synthetic characteristics and determining its place and role in conducting negotiation processes in a company. In the summing up section of the paper the conclusions from the considerations are presented as well as the directions of further studies are indicated.